The Development of Playstore-Based German Speaking Skills with German Conversation Practice Application Hallo - Insenalia Sampe Roly Hutagalung (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to identify the need for German language teaching materials for class XII students at HKBP Pematangsiantar High School. The type of research used is qualitative with a qualitative descriptive approach. Data collection techniques used are interviews and questionnaires. Needs analysis in this study uses the theory of Briendley, Hutchinson and Waters, and the theory of Nation and Macalister by dividing the needs analysis into objective needs and subjective needs. Objective needs include the identification and background of students, while subjective needs include needs, deficiencies, and desires. The results of the study indicate that the teaching materials that have been used so far are not enough, but the need to look at the needs of students in improving the four abilities that lead to 21st century learning. The teaching materials expected by students are teaching materials that have text, images, animation, audio, audiovisuals as well as independent German speaking exercises. Students also want teaching materials that are easy to carry and accessible at any time.